1999
DOI: 10.7547/87507315-89-10-506
|View full text |Cite
|
Sign up to set email alerts
|

Household-shoe wearing and purchasing habits. A survey of people aged 65 years and older

Abstract: A mail survey was conducted to assess the types of household footwear currently being worn by a random sample of independently living men and women aged 65 years and older as well as their needs related to the purchase and wearing of household footwear. Questionnaires were completed by 128 people. The greatest number of respondents wore slippers all day around the home, purchasing these shoes because of their convenience and comfort. Respondents were not willing to purchase expensive shoes for household wear a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 11 publications
2
38
1
Order By: Relevance
“…Between 26 and 50% of older people wear shoes that are too short or too narrow [61][62][63] due to fashion influences [64,65], not measuring foot dimensions when purchasing shoes [66], and the limited availability of footwear that adequately caters for the altered morphology of the older foot [67,68]. In older people, wearing shoes substantially narrower than the foot is associated with corns on the toes, hallux valgus deformity and foot pain, whereas wearing shoes shorter than the foot is associated with lesser toe deformity [69].…”
Section: Footwear Considerationsmentioning
confidence: 99%
“…Between 26 and 50% of older people wear shoes that are too short or too narrow [61][62][63] due to fashion influences [64,65], not measuring foot dimensions when purchasing shoes [66], and the limited availability of footwear that adequately caters for the altered morphology of the older foot [67,68]. In older people, wearing shoes substantially narrower than the foot is associated with corns on the toes, hallux valgus deformity and foot pain, whereas wearing shoes shorter than the foot is associated with lesser toe deformity [69].…”
Section: Footwear Considerationsmentioning
confidence: 99%
“…Although previous research has shown that 5 weeks of habituation to new shoes does not significantly affect standing balance or gait in older women [40] , it may take longer for this to occur. Second, because women are more likely to wear slip-on indoor footwear [8] and fall indoors [7] , we specifically recruited older women into the study, so we cannot be certain that the findings are generalisable to older men. Third, it could be argued that older women at a higher risk of falling may have been a more appropriate target sample.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, half of all falls occur inside the home, and older people who fall indoors are more likely to be female, older, less physically active and to have poorer general health [7] . Secondly, indoor footwear tends to be less supportive than outdoor footwear, is infrequently replaced, and is selected primarily for comfort [8] . The most frequently worn indoor footwear is slippers, which often comprise design features considered detrimental to balance, including lack of fixation, thick, soft midsoles, and smooth outsoles [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older adults who live in the community preferably wear slippers, socks, or no shoes at home. 9 In residential settings, as well as with increasing age, the "slipper-mania" is even greater. 10 However, these types of footwear (or no footwear) have previously been identifi ed as fall risk factors [11][12][13] and have even been associated with increased injurious falls.…”
Section: Introductionmentioning
confidence: 98%